2023
DOI: 10.1001/jamaoto.2023.1283
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Analysis of Caregiver Burden in Head and Neck Cancer

Abstract: ImportanceDespite the critical role of caregivers in head and neck cancer (HNC), there is limited literature on caregiver burden (CGB) and its evolution over treatment. Research is needed to address evidence gaps that exist in understanding the causal pathways between caregiving and treatment outcomes.ObjectiveTo evaluate the prevalence of and identify risk factors for CGB in HNC survivorship.Design, Setting, and ParticipantsThis longitudinal prospective cohort study took place at the University of Pittsburgh … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Considering that FCs with higher education have better comprehension ability, they can better master and understand disease knowledge and nursing skills. 41 Schandl, et al 42 suggests that FCs with lower levels of education are more likely to have uncertainties about the disease and anxiety and depression, and they may have limited ability to find or use helpful resources.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that FCs with higher education have better comprehension ability, they can better master and understand disease knowledge and nursing skills. 41 Schandl, et al 42 suggests that FCs with lower levels of education are more likely to have uncertainties about the disease and anxiety and depression, and they may have limited ability to find or use helpful resources.…”
Section: Discussionmentioning
confidence: 99%
“…Although less studied, caregivers also experience FT due to employment disruptions and loss of income during caregiving. Beyond financial worries, caregivers are also at risk of developing health problems, with caregivers of nonworking patients having the highest risk …”
mentioning
confidence: 99%
“…Furthermore, caregiver strain can also manifest in physical reactions such as fatigue and hypervigilance. Various sustainable interventions (Chow et al 2023b;Kudrick et al 2023) have been suggested to address their needs, including face-to-face and telehealth-based training programs, education on the impact of caregiving, coping strategies, self-care approaches, and assistance with organizational planning facilitated by social workers. By implementing these interventions, caregivers will receive the necessary assistance and resources to address their challenges and improve their well-being.…”
mentioning
confidence: 99%